2020
DOI: 10.3390/toxins12060415
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Enniatin B1 and Its Phase I Metabolites in Human Urine: First Large-Scale Study

Abstract: Enniatins (Enns) are mycotoxins produced by Fusarium spp. which are a fungus widely spread throughout cereals and cereal-based products. Among all the identified enniatins, Enn B1 stands as one of the most prevalent analogues in cereals in Europe. Hence, the aim of this study was to evaluate for the first time the presence of Enn B1 and its phase I metabolites in 300 human urine samples using an ultrahigh-performance liquid chromatography high resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS) methodology. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…There are no data on the distribution of enniatins in WW, but enniatins have been frequently found in urine samples. Enniatin B has been detected in urine at 0.006 to 0.391 ng/mL concentrations [22] and enniatin B1 was detected at 0.007 to 0.429 ng/mL [23]. It should be considered that these studies were from Italy where the occurrence of enniatin may be different than in the northern Europe.…”
Section: Occurrence Of Mycotoxins In Wastewatermentioning
confidence: 90%
See 1 more Smart Citation
“…There are no data on the distribution of enniatins in WW, but enniatins have been frequently found in urine samples. Enniatin B has been detected in urine at 0.006 to 0.391 ng/mL concentrations [22] and enniatin B1 was detected at 0.007 to 0.429 ng/mL [23]. It should be considered that these studies were from Italy where the occurrence of enniatin may be different than in the northern Europe.…”
Section: Occurrence Of Mycotoxins In Wastewatermentioning
confidence: 90%
“…Mycotoxins of the ENN group have been frequently detected in human blood serum and urine. Thus, in two studies from Italy [22,23], enniatin B1 was observed of 84% and 94% of urine samples in the range of 0.006-0.391 ng/mL and 0.007-0.429 ng/mL, respectively. Enniatin B was frequently detected in urine samples [35], with the average concentration of 0.017 ng/mL.…”
Section: Wastewater Based Epidemiology For Tracking Human Exposure To...mentioning
confidence: 93%
“…[37,38]. ENNs occur as contaminants mainly in cereals, although their presence has been also reported in other matrices, including products of animal origin, as a consequence of the carry-over of these compounds into animal tissues after the feeding of contaminated feed [39][40][41][42][43][44][45]. As reported, high contamination levels of ENNs in food commodities have been reported.…”
Section: Enniatin Bmentioning
confidence: 99%
“…However, all four EN analogs were detected in feces with maximum concentrations 6 h after administration [23]. Further studies are needed to specify the routes of ENs and BEA excretion in livestock animals and also check the presence of various phase I metabolites in excreta because demethylated, oxidated, hydroxylated and carbonylated metabolites were recently tentatively identified in human urine samples [121].…”
Section: Metabolism Of Beauvericin and Enniatinsmentioning
confidence: 99%